Construyendo movimientos ecoterritoriales en áreas de conservación privado-comunitarias - Flores-Fernandez, Vera Alejandra; Van den Broeck, Pieter; Hermans, Elke; Parra, Constanza (Pontificia Universidad Católica del Perú, 2024)
Nature conservation is an urgent issue globally, particularly regarding its integration with sustainable socio-economic development. In Latin America, countries like Peru face increasing tensions between nature conservation and neoextractivist models. The eco-territorial turn of socio-environmental movements in the region reflects a critique of this economic model and seeks collective governance of the territory. In this context, Private Conservation Areas (PCAs) have proliferated in recent decades, with the Chaparrí Nature Reserve pioneering as the first private-community PCA led by a peasant community. The case of Chaparrí illustrates the struggle between local conservationists and proponents of extractivist development. This article explores the eco-territorial movement generated in Chaparrí from the activist research that brought together efforts with Belgian and Peruvian academics and students. The eco-territorial movement in Chaparrí has not only catalyzed transformations in community dynamics but also collaborations with a wide range of actors. The scholars from the activist research managed to integrate into the landscape of actors and institutions revolving around Chaparrí, opening new and innovative opportunities for collaboration.

Resumen La conservación medioambiental es un tema urgente a nivel mundial, en particular en cuanto a su integración con el desarrollo socioeconómico sostenible. En Latinoamérica, países como Perú enfrentan crecientes tensiones entre la conservación ambiental y modelos neoextractivistas. El giro ecoterritorial de los movimientos socioambientales en la región refleja una crítica a esta economía y busca una gobernanza colectiva del territorio. En este contexto, las Áreas de Conservación Privada (ACP) han proliferado en las últimas décadas, y la Reserva Ecológica de Chaparrí es pionera al ser liderada por una comunidad campesina. El caso de Chaparrí ilustra esta lucha entre conservacionistas locales y defensores del desarrollo extractivista. En este artículo se explora el movimiento ecoterritorial generado en Chaparrí desde una investigación activista que congregó este esfuerzo con académicos y estudiantes belgas y peruanos. El movimiento ecoterritorial de Chaparrí no solo ha catalizado transformaciones en las dinámicas comunitarias, sino también en colaboraciones con una gran variedad de actores. Los investigadores lograron integrarse al paisaje de actores e instituciones que gravitan en torno a Chaparrí, abriendo nuevas e innovadoras oportunidades de colaboración.
Building Eco-Territorial Movements in Private-Community Conservation Areas
Keywords: Protected areas; Community conservation; Ecotourism; Áreas Naturales Protegidas; Conservación comunitaria; Ecoturismo; https://purl.org/pe-repo/ocde/ford#5.04.00